Assistance in Obtaining Halal Certification (Self-Declaration) for Sweet Hony Canteen at Mulawarman University - Sumadi, Lalu Aditya; Utoro, Panggulu Ahmad Ramadhani; Pujokaroni, Agustu Sholeh; Andriyani, Yulian; Banin, Maghfirotin Marta; Suprapto, Hadi; Rohmah, Miftakhur (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2024)
Halal food is increasingly important for both Muslims and non-Muslims due to its cleanliness and health benefits. Halal certification, regulated by Law No. 33 of 2014 on Halal Product Assurance, is essential for building consumer trust, expanding markets, and boosting company sales. It is particularly crucial for MSMEs, such as food stalls, as it impacts both trust and revenue. This community service project helped the Sweet Hony canteen obtain halal certification through socialization, interviews, and document preparation, supported by students, Field Supervising Lecturers (FSL), and the Halal Research Center at Mulawarman University. The effort led to the issuance of a Business Identification Number (BIN) and an ongoing halal certification process.